Prenatal presentation of glutaric aciduria type II: A case report with radiologic, clinical, biochemical, molecular, and pathological phenotyping. Issue 3 (12th January 2021) - Carmant, Laurence; Karalis, Aspasia; Rypens, Françoise; Oligny, Luc; Wavrant, Sandrine; Lapeyraque, Anne‐Laure; Codsi, Elisabeth
Abstract: We know that glutaric aciduria type II is an inborn metabolism. This case report highlights that polycystic kidneys with hepatomegaly in prenatal ultrasound are suggestive of glutaric aciduria type II and it identifies a new variant as pathogenic. Abstract : We know that glutaric aciduria type II is an inborn metabolism. This case report highlights that polycystic kidneys with hepatomegaly in prenatal ultrasound are suggestive of glutaric aciduria type II and it identifies a new variant as pathogenic.